2002
DOI: 10.21836/pem20020602
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy examination of tendon biopsies in healthy horses and patients with different stages of tendon healing.

Abstract: EinleitungErkrankungen der Beugesehnen stellen bei Sportpferden aufgrund des langwierigen Heilungsverlaufes und der hohen Rezidivneigung ein bedeutendes orthopädisches Problem dar. Scanning electron microscopy examination of tendon biopsies in healthy horses and patients with different stages of tendon healing.In this study core biopsies of 12 healthy flexor tendons and 40 flexor tendons at different stages of tendopathia (tendonitis) were investigated. The biopsy was taken in vivo with an automatic biopsy dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…They were also similar to those described by Buck et al (2002), who observed a significant difference in texture-values comparing control and tendonitis groups. The altered consistency in tendon tissue samples obtained in the present study could be explained initially due to inflammation, with collagen degeneration and necrosis (24-96 h after injury), and due to immature and disorganised collagen fibers at later phases (15-150 days after injury).…”
Section: Tendon Tissue Macroscopic Evaluationsupporting
confidence: 90%
See 2 more Smart Citations
“…They were also similar to those described by Buck et al (2002), who observed a significant difference in texture-values comparing control and tendonitis groups. The altered consistency in tendon tissue samples obtained in the present study could be explained initially due to inflammation, with collagen degeneration and necrosis (24-96 h after injury), and due to immature and disorganised collagen fibers at later phases (15-150 days after injury).…”
Section: Tendon Tissue Macroscopic Evaluationsupporting
confidence: 90%
“…These two techniques were performed under general anaesthesia, and as described by Maia et al (2009), a tenorrhaphy was needed to restore the tendons, complicating the outcomes and enabling the collection of only one fragment per limb. Buck et al (2002) used a biopsy device, similar to that used in this study, to collect flexor tendon fragments. However, the harvested fragments were longer (1.6cm long), the horses outcome after the procedure were not evaluated and the authors did not perform serial collections.…”
Section: Ultrasonographic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon biopsies were used because clinical assessment of tendon healing and B-mode ultrasonography alone are limited with regard to sensitivity and reproducibility [ 40 ] and longitudinal needle biopsies were established in human [ 41 , 42 ] and equine surgery [ 29 , 43 ] as minimally invasive and well-tolerated techniques. They allow an insight into tendon architecture as well as the immunohistochemical detection of, for example, collagen type I and III [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…They allow an insight into tendon architecture as well as the immunohistochemical detection of, for example, collagen type I and III [ 44 ]. Disadvantages, however, are the potentially therapeutic, albeit unknown, effect of the biopsy process on tendon healing [ 2 , 45 ], their limited reproducibility and the relatively small volume of tendon tissue harvested [ 29 , 43 ].…”
Section: Discussionmentioning
confidence: 99%